Production Failure: Product Quality Control Review as a Potential Research Activity and Community Service - Emma Budi Sulistiarini; Alfiana Alfiana; Nurida Finahari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Production control is an important aspect in a company. Control management is carried out as an effort to reduce and prevent product failures or defects. The purpose of writing this article is to review production failures through product quality control. The results of the review can be used as a situational analysis study for community service activities, especially for industrial engineering. The review is carried out by searching the literature for national publications over the last 10 years. The summary of the research is carried out by grouping based on the category of control method used, the field of study or product being studied and the results of the research. The results of the analysis show that the FMEA (Failure Mode and Effect Analysis) method is widely used in case studies in manufacturing companies. Further research can be carried out to compare the application of the method to similar case studies. Community service activities in this field can be directed to implement the FMEA method for target partners for types of businesses that carry out production processes, goods, and services.